An Experimental Study of Stagger Angle Effect Placed in front of Returning Side toward the Savonius Wind Performance Using Overlap Myring Blade for n = 1 - Setiawan, Priyo Agus; Lukitadi, Projek P. S.; Santoso, Emie; Ariwiyono, Nopem; Sa’diyah, Aminatus; Antariksih, Daisy D. K. R.; Anindita, Galih; Prasojo, Budi; E. Kusuma, George; Indarti, Rini; Santoso, Mardi; Antoko, Bambang; Purwanti, Endang P.; M. Munir, Mohammad (International Journal of Marine Engineering Innovation and Research, 2025)
The previous Savonius wind turbine studies have proved that overlap modifications to conventional blades can improve turbine performance. With these conventional blades, the performance is less optimum because the drag force generated by turbine's rotation is still high. Based on this condition, this experiment is conducted by modifying Savonius wind turbine with overlap blades using Myring equation n = 1. Its blade profile is made half-elliptical to reduce drag force. Diameter and height of the turbine are 400 mm with 0.3 overlap ratio. The ratio of cylinder diameter (ds/D) is 0.4, and the ratio of cylinder center distance (S/d) is 1.7. Experiments are conducted by varying stagger angles of circular cylinder in front of returning blade are 45°, 50°, 55°, and 60° with velocity 5 m/s. The final results show that the best performance improvement of the turbine occurs at 60° stagger angle. The increase in torque coefficient is 4.95% and power coefficient is 20.16% to overlap Savonius wind turbine with myring n = 1 with no circular cylinder.